Sequential Congruency Effects in Monolingual and Bilingual Adults: A Failure to Replicate Grundy et al. (2017) - Goldsmith, Samantha F.; Morton, J. Bruce (Frontiers in Psychology, 2018)
Previous research suggests bilingual adults show smaller sequential congruency effects than monolingual adults. Here we re-examined these findings by administering an Eriksen flanker task to monolingual and bilingual adults. The task produced robust conventional and sequential congruency effects. Neither effect differed for monolingual and bilingual adults. Results are discussed in terms of current debates concerning differences in cognitive control of monolingual-bilingual adults.